Designing and Implementing Performance Technology for Teachers - Joi L. Moore (The Canadian Network for Innovation in Education (CNIE), 2004)
This paper synthesizes research findings from a performance analysis of teacher tasks and the implementation of performance technology. These findings are aligned with design and implementation theories to provide understanding of the complex factors and events that occur during the implementation process. The article describes the necessary elements and conditions for designing and implementing performance tools in school environments that will encourage usage, efficient performance, and positive attitudes. Two models provide a visual representation of causal relationships between the implementation factors and the technology user. Although the implementation process can become complex because of the simultaneous events and phases, it can be properly managed through good communication and strategic involvement of teachers during the design and development process. The models may be able to assist technology designers and advocates with presenting innovations to teachers who are frequently asked to try technical solutions for performance support or improvement.